Chattering-suppression sliding mode control of an autonomous underwater vehicle based on nonlinear disturbance observer and power function reaching law. (June 2021) - Tang, Qirong; Li, Yinghao; Guo, Ruiqin; Jin, Daopeng; Hong, Yang; Huang, Hai
To improve the performance of autonomous underwater vehicle in trajectory tracking control, which is subject to system uncertainties and time-varying external disturbances, a nonlinear disturbance observer-based sliding mode controller is proposed in the study. First, a reaching law with a special power function and a hyperbolic tangent function is presented. Then an improved sliding mode controller based on the new reaching law is combined to decrease the reaching time and avoid chattering during the trajectory tracking control. Furthermore, to reduce the influence of the system uncertainties and external disturbances, a nonlinear disturbance observer is introduced to identify them. The error asymptotic convergence of the trajectory tracking control is proved by the Lyapunov-like function. Finally, under different environmental disturbances, plenty of simulations are carried out to verify the efficiency and robustness of the proposed method. Results show that when it is tracking different trajectories, the proposed method can suppress the chattering and reduce the disturbances effectively, while ensuring tracking performance.